2022
DOI: 10.1002/fld.5125
|View full text |Cite
|
Sign up to set email alerts
|

Research on grid‐dependence of neural network turbulence model

Abstract: Turbulence machine learning based on deep neural network has become a research hotspot in turbulence modeling. Although most turbulence models have strict requirements on grid dependence, there are few analyses on grid dependence on the coupling of models and equations. In this article, a neural network turbulence model is constructed for the flow around airfoil with high Reynolds number, and the effects of wall‐normal grid spacing on the calculation accuracy are studied. The results show that compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The studies that focused on RANS model augmentation can be further subdivided into three categories: (i) direct estimation of the turbulent eddy viscosity ( 𝑇 ) for linear models [47][48][49][50][51][52][53][54][55], (ii) correction terms for the linear models [56][57][58][59][60][61][62][63], and (iii) enhancement of the accuracy of the turbulence transport equations used in linear models [64][65][66][67][68]. Studies in category (i) have been applied for both incompressible [47][48][49][50] and compressible flows [51][52][53][54]. They have either used neural networks with two to six hidden layers with 20 to 40 neurons per layer or random forest models with three to four hidden layers with 64 to 128 trees.…”
Section: Kaandorp and Dwightmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that focused on RANS model augmentation can be further subdivided into three categories: (i) direct estimation of the turbulent eddy viscosity ( 𝑇 ) for linear models [47][48][49][50][51][52][53][54][55], (ii) correction terms for the linear models [56][57][58][59][60][61][62][63], and (iii) enhancement of the accuracy of the turbulence transport equations used in linear models [64][65][66][67][68]. Studies in category (i) have been applied for both incompressible [47][48][49][50] and compressible flows [51][52][53][54]. They have either used neural networks with two to six hidden layers with 20 to 40 neurons per layer or random forest models with three to four hidden layers with 64 to 128 trees.…”
Section: Kaandorp and Dwightmentioning
confidence: 99%
“…Some studies identified additional advantages of the ML approach, e.g., Maulik et al [49] reported that ML  𝑇 estimation sped up simulation time by 100% compared to the two-equation RANS model. Song et al [54] reported that ML turbulence model had more lenient near-wall y + requirements compared physics-based models, and thus required smaller grid sizes and lower computational costs.…”
Section: Kaandorp and Dwightmentioning
confidence: 99%